Sangamonian Forest History and Climate in Atlantic Canada - Mott, Robert (Géographie physique et Quaternaire, 1990)
ABSTRACTSeven of the more than twenty five buried organic deposits in Atlantic Canada assigned to pre-Wisconsinan non-glacial intervals possibly relate to the climatic optimum of the Sangamon Interglaciation, that is substage 5e of the deep-sea oxygen isotope record. These sites are East Bay and Green Point on Cape Breton Island. Addington Forks and East Milford in mainland Nova Scotia. Le Bassin and Portage-du-Cap on the Iles de la Madeleine, Québec, and Woody Cove, Newfoundland. Except for Woody Cove, none of the sites records a complete climatic cycle, and the sequence of events must be pieced together from their disparate records. The spectra, characterized by significant amounts of thermophilous taxa that are not as abundant or present in the region today, are similar in general to Holocene spectra at sites immediately south of the lower Great Lakes. Comparison of the fossil spectra from five sites with modern surface spectra from eastern North America yields modern analogs which, if valid, indicate that the climate in Atlantic Canada during the climatic optimum of the last interglacial interval was more continental in character and considerably warmer than present.